Pengaruh Kurangnya Komunikasi Antara Anak dan Orang Tua yang di Sebabkan Oleh Perceraian - Keysa Khalidaziah; Nina Yuliana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Divorce is a complex social phenomenon and can have a significant impact not only on divorced couples but also on the families involved, especially children who are an integral part of family dynamics. One aspect that can be affected by divorce is communication between children and parents. This study uses a qualitative approach to gain in-depth insight into how divorce affects communication between parents and children. The divorce of a parent can cause stress, stress, and depression leading to physical and psychological changes for family members. (Dagun, 1990 dalam Dewi Herdiyanto, 2018). The family is a parent whose social function is to bring the child into a more genuine and wider social life. (Amirulloh, 2015 dalam Kobandaha, 2019). From the above view, it can be concluded that marriage has a very important dimension in forming a happy and lasting family, as described in the law. Husbands and wives play a role in creating a peaceful, peaceful and loving life, forming the foundation of a prosperous family.